Sickle Cell Anemia In Sheedi Population of Lyari: Hemoglobinopathy Seen in a Neglected Population - Sameen, Durr e (International Journal of Pathology, 2019)
Background: Hemoglobinopathies are global health burden. Some geographical areas are more severely hit by this problem than others, this is partly related to the genetics and partly to the custom of inter-marriages seen in some populations. Counseling could play an important determinant in combating the increased incidence of hemoglobinopathies by reducing family inter-marriages.Material & Methods: This descriptive cross-sectional study was conducted in Lyari General Hospital Karachi for six months. Two hundred(200) subjects of Sheedi/Makrani populationwere inducted and Complete blood |Count (CBC) with Red blood cell indices and absolute values, peripheral smear and electrophoresis was performed.Results: Most of the study participants were females with female to male ratio of 1:0.59. Out of 200 study participants, 9% (n=18) were found to be Sickle carriers, while 5% (n=10) were found to have Sickle cell disease with total frequency was 14% in the study population.Conclusion: Sickle cell anemia was found to be affecting 14% of study population belonging to the Sheedi/Makrani caste residing inLyari. High percentage of interfamily marriages relates as one of the possible reasons of high frequency of Hemoglobinopathies in that cast.